(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
A study was conducted in the experimental field of the Institute of Forage Crops – Pleven on a slightly leached chernozem soil in 2011-2012 to determine the selectivity of some herbicides to standard wheatgrass (Agropyron desertorum (Fisch.) Schultes) during stand establishment and its seed production. The study had the following results: the herbicides Kambio SL (320 g/l bentazone + 90 g/l dicamba) – 1250 ml/ha; Kalam (125 g/l tritosulfuron + 600 g/kg dicamba) – 200 g/ha; Lintur 70 WG (4.1% triasulfuron + 65.9% dicamba) – 150 g/ha, and Axial 050ЕK (50 g/l pinoxaden) – 600 ml/ha showed high selectivity to standard wheatgrass when applied at the stage of 3-4 leaves during the year of stand establishment; the herbicides Imaspro (69 g/l fenoxaprop-P-ethyl+antidote) and Stelar (50 g/l topramezone + 160 g/l dicamba), each applied at the rate of 1000 ml/ha, caused phytotoxicity (scores from 4 to 6), while Termidor (40 g/l nicosulfuron) – 1250 ml/ha completely destroyed the crop (score 9); the herbicides Kambio SL; Kalam; Lintur 70WG and Axial 050ЕK applied at the same doses at the stage from spring growth to the beginning of shooting up in the seed production year had a high selectivity to standard wheatgrass and could be applied in seed production stands without negative influence on seed productivity. The herbicide Termidor was very phytotoxic (scores from 3 to 7) and prevented the formation of generative stems.